PENGARUH METODE INKUIRI BERBASIS SAINS TEKNOLOGI MASYARAKAT TERHADAP HASIL BELAJAR IPS: Studi Quasi Eksperiment Terhadap Peserta Didik Kelas VII di SMP Negeri 1 Bandung - Suryani, Yani (2013)
The background of this research is the issue of globalization that impact on society's lives, especially school-age children (students) who started to use the technology in every activity. The problem in this study is whether the method of inquiry - based on Science Technology and Society has a significant effect on social science learning outcomes of students in SMPN 1 Bandung. This study use quasi-experimental approach, with nonequivalent (pretest and posttest) the Control Group Design. The average result of experimental class' pre-test is 59.72, and the post-test average is 77.08, the gain is 0, 46, While in the control classroom the average of pre - test is 56.81, and the post-test is 68.75, and the gain is 0, 28. There seems to be a significant improvement between the experimental class and the control class. The results were analyzed using the data analysis software called SPSS 16 for windows shows the sig is 0.000 < α 0.05, which means the test results showed that Ho strongly rejected, means that there are some learning outcomes distinctions between the student who get a method of inquiry -based learning with Science Technology and Society Methods with those who received conventional learning at the post-test. Post-test results of the students who received inquiry -based learning with the Science Technology and Society Methods is better than the students who received conventional learning. It can be seen from the motivation to learn, learner inquiry frequency, the students learning outcomes in land use and settlement patterns material based on the physical condition of the earth's surface. The recommendations were based on the research findings and the discussion of the effect of the use of inquiry -based science technology society method. It is expected that schools, Social Sciences' MGMP, social science Teacher and the next researcher can use and develop the inquiry -based science learning technology methods community in the social science. Keywords : Inquiry -based science learning technology methods, Learning Outcomes, Social Science Learning Latar belakang penelitian ini adalah masalah globalisasi yang berdampak terhadap kehidupan masyarakat , khususnya anak usia sekolah(peserta didik) yang mulai banyak memanfaatkan teknologi dalam setiap kegiatan. Permasalahan dalam penelitian ini yaitu apakah metode inkuiri berbasis STM memiliki pengaruh signifikan terhadap hasil belajar IPS peserta didik di SMP N 1 Bandung. Bentuk penelitian ini adalah quasi eksperiment, dengan desain nonequivalent (pretes dan postest) Control Group Design. Hasil nilai kelas eksperimen pre-test rata-rata 59.72, nilai post-test rata-rata 77.08, gain 0.46 dan di kelas kontrol pre-test rata-rata 56.81, nilai post-test 68.75 , gain 0.28. Terlihat ada peningkatan yang signifikan antara kelas eksperimen dan kelas kontrol. Hasil analisis data dianalisis dengan menggunakan Software SPSS 16 for windows sig sebesar 0,000 < α 0,05 , yang berarti hasil uji menunjukkan sangat kuat menolak Ho, artinya terdapat perbedaan hasil belajar peserta didik antara peserta didik yang mendapatkan pembelajaran dengan metode inkuiri berbasis STM dan peserta didik yang mendapatkan pembelajaran konvensional pada pengukuran akhir (post-test). Hasil post-test peserta didik yang mendapatkan pembelajaran dengan metode inkuiri berbasis STM lebih baik dari peserta didik yang mendapatkan pembelajaran konvensional. Hal ini dapat dilihat dari motivasi belajar, frekwensi peserta didik bertanya, hasil belajar peserta didik dalam materi penggunaan lahan dan pola permukiman berdasarkan kondisi fisik permukaan bumi. Rekomendasi berdasarkan temuan penelitian dan pembahasan mengenai pengaruh penggunaan metode inkuiri berbasis sains teknologi masyarakat. Diharapkan pihak sekolah, MGMP IPS, Guru bidang studi IPS dan peneliti selanjutnya dapat menggunakan dan mengembangkan metode Inkuiri berbasis sains teknologi masyarakat dalam pembelajaran IPS. Kata Kunci : Metode Inkuiri Berbasis STM, Hasil Belajar, Pembelajaran IPS